Importance and practices of Egusi crops (Citrullus lanatus (Thunb.) Matsum. & Nakai, Cucumeropsis mannii Naudin and Lagenaria siceraria (Molina) Standl. cv. Aklamkpa) in sociolinguistic area in Benin - Achigan-Dako, Enoch G.; Fagbemissi, R.; Avohou, H.T.; Vodouhe, R.S.; Coulibaly, O.; Ahanchédé, A. (2008)
African traditional vegetables are perceived as potentially useful for income generation and food security insurance. However, Egusi crops (Citrullus lanatus subsp. mucosospermus, Cucumeropsis mannii and Lagenaria siceraria cv. ' Aklamkpa ') have been overlooked for relatively long time by research and development organizations while they persist in the farming systems of many regions in West Africa. This paper pinpoints the social importance of Egusi crops and their place in the cropping systems in sociolinguistic groups in Benin. In 2005, a countrywide household survey in Benin on farming systems and cropping practices of Egusi crops across five major sociolinguistic groups show that Egusi is ranked among the top ten crops. This ranking is gender-specific but is not age-specific. Farmers allocated on average 0.74 ha for Egusi production with a significant difference across communities. In the Mahi-fon community in central Benin for instance farm size could reach 5 ha. The most cultivated species is C. lanatus subsp. mucosospermus. However, in the Adja community the farmers' preference is for L. siceraria cv. ' Aklamkpa '. Egusi species are cultivated in plain field or in home gardens, either in monoculture or in association with other crops. C. mannii is mostly intercropped and plays a social and culinary role in Nagot-Yoruba community. Although Egusi is not a specific woman crop, women carry out the post-harvest activities for value adding. Utilizations of Egusi crops are different from one sociolinguistic group to another and could represent a plinth on which a sustainable valuation of Egusi crops could be developed.